Greening Turku: A Vision for a Greener and and Sustainable Historic Town 2019 - Ana Maria Jones; Markku Wilenius (University of Turku, FFRC, 2022)
The Green-in TURKU project, originally titled as Towards a Greener Urban Future, has been an investigation towards innovative solutions to increase liveability in the inner city of Turku. The project idea stemmed from Turku Vision for the City Centre 2050, a project chaired by Prof. Markku Wilenius in the years 2016-2017. The Vision was well received by the public and political decision-makers alike. As a result, developing a more detailed plan on key priority areas was thought to be useful to push the progress of the city centre design to the forefront. A central theme, that came already well forward during the vision work, was the current state of green areas. That meant not only parks and gardens but actually the reinvigoration of the city core to meet the needs of a new urban generation, appreciative of social and ecological environments over cars, concrete-dominated landscapes and opportunistic economic reasoning. Together with the city authorities, a more qualitative research and urban analysis of Turku’s urban structure was conducted by the Germany-based resource efficiency planner Ana Jones. The purpose of the project was to investigate innovative strategies, identify challenges and formulate new pathways for how to scale-up usability and access to green areas in the city centre of Turku.